Applicablity of an indirect method to predict maximum oxygen uptake in young badminton players of Nepal - Chatterjee. P.; Banerjee, A. K.; Das, P. (International Journal of Sports Science and Engineering, 2010)
The aim of the study was to validate the applicability of the 20-m Multi Stage Shuttle Run Test (20-m MST) in young badminton players of Banke district, Nepal. For application of direct method "cross-over design" (random sequencing) was followed. For validity of the results, repeatability was investigated where 24 subjects performed the test (20-m MST) twice. Intra-class correlation coefficients (ICC) were used to determine test-retest reliability. Forty young badminton players (age range 12 ~ 17 years, sex- male) from different sports academies of Banke district, Nepal were recruited for the study. Direct estimation of maximal oxygen consumption (VO2 max) comprised of treadmill exercise followed by expired gas analysis by scholander micro-gas analyzer, whereas VO2 max was indirectly predicted by 20-m MST. The difference between the mean ( ± standard deviation) VO2 max values of direct measurement (VO2 max = 46.85 ± 3.90 ml/kg/min) and the 20-m MST [Shuttle predicted VO2 max (SPVO2 max) = 46.08 ± 3.88 ml/kg/min] was statistically significant. The results suggest that the application of the present form of 20-m MST may not be justified in the studied population. For better prediction of VO2 max a new equation has been developed based on present data. The new equation is recommended to be used for the studied population.